Cross-omics analysis reveals microbe–metabolism interactions characteristic of gingival enlargement associated with fixed orthodontic in adolescents - Yang Lv; Sisi Peng; Yali Liu; Hefeng Yang; Guiding Li; Yi Peng (Journal of Oral Microbiology)
Objectives To investigate the oral microbiome and metabolome longitudinal changes associated with orthodontic treatment-induced gingival enlargement (OT-GE).Methods Twenty-six subjects were divided into case and control groups based on the gingival overgrowth index (GOi). The OT-GE group was divided into the no gingival enlargement (OT-GE0, n = 5) and persistent gingival enlargement (OT-GE1, n = 11). The control group included orthodontic treatment periodontal health (OT-GH, n = 5), and no orthodontic treatment periodontal health (NOT-GH, n = 5). Microbial composition and metabolites in saliva were investigated using cross-omics.Results Longitudinal analysis linked orthodontic treatment-induced gingival enlargement to distinct oral microbiome and metabolome shifts. The OT-GE group showed significantly higher bleeding on probing (BOP), plaque scores (p < 0.001), probing depth, GOi, and ligature wire differences (p < 0.05) versus controls. Microbial diversity and species richness were elevated in OT-GE (p < 0.05), though no differences emerged between OT-GE0 and OT-GE1) subgroup (p > 0.05). Cross-omics identified specific periodontal pathogens and metabolites linked to gingival enlargement. Disrupted amino acid biosynthesis pathways, particularly citrulline metabolism, correlated with functional gene dysregulation and microbial imbalance. Aberrant citrulline intake appeared to drive dysbiosis, potentially contributing to gingival overgrowth.Conclusions OT-GE pathogenesis involves functional gene-regulated metabolite metabolism influencing periodontal pathogens.